Concomitant Upper Extremity Fracture Worsens Outcomes in Elderly Patients With Hip Fracture. (1st June 2018) - Thayer, Mary Kate; Kleweno, Conor P.; Lyons, Vivian H.; Taitsman, Lisa A.
Background: Elderly patients with low-energy hip fractures have high rates of morbidity and mortality, but it is not well known how often concurrent upper extremity fractures occur and how this impacts outcomes. We used the National Trauma Databank (NTDB), the largest aggregation of US trauma registry data available, to determine whether patients with concurrent upper extremity and hip fractures have worse outcomes than patients with hip fractures alone. Methods: We accessed the NTDB to identify patients aged 65 to 100 who sustained a hip fracture. The cohort was then narrowed to include only patients who sustained their injury in a fall and had an injury severity score indicating hip fracture as the most severe injury. We then analyzed this group to assess the impact of a simultaneous upper extremity fracture on length of stay, in-hospital mortality, and discharge disposition. Results: From 2007 to 2014, a total of 231, 299 patients aged 65 to 100 were identified as having a hip fracture. The narrowed cohort with fall as the mechanism and hip fracture as the most severe injury included 193, 862 patients. Of these, 12, 618 patients sustained a concomitant upper extremity fracture (6.5%). Compared to isolated hip fractures, patients with a concomitant upper extremity fracture had higher odds of death in the hospital (odds ratio [OR] = 1.3; 95% confidence interval = 1.2-1.4), were less likely to be discharged to home as compared to a skilled facility (OR = 0.73; 95% confidence interval = 0.68-0.78), and had a significantly longer average length of stay (7.1 vs 6.4 days, P < .001). Conclusions: We found a 6.5% prevalence of concomitant upper extremity fractures in patients aged 65 to 100 with a hip fracture sustained after a fall where the hip fracture was the most severe injury. These patients had a higher risk of in-hospital mortality, were less likely to be discharged to home, and had longer average length of stay.